Análise da Revised Trauma Score (RTS) em um centro de trauma tipo III na rede de saúde de urgência e emergência do município de Fortaleza - Falcão, Rita de Souza Tomás (Universidade Federal Rural do Semi-Árido, 2020)
Trauma is the main cause of death in the population aged 1 to 44 years, mostly men. In this context, trauma scores are mathematical models that aim to describe the influence of a wide range of conditions of the severity of a trauma, correlating them with the probability of complications and prognosis. From this perspective, the Revised Trauma Score (RTS) is a trauma score capable of evaluating the morbidity and mortality of multiple trauma patients and directing the approach to that of the patient. Thus, the objective was to analyze the application of RTS in a type III trauma center in the urgency and emergency health network in the city of Fortaleza/CE. For this purpose, 126 medical records of patients admitted to the Instituto Doutor José Frota (IJF) were selected, with a predominance of males. As for the trauma mechanism, there was a prevalence of 68.1% of blunt trauma, with a predominance of automobile accidents. Among the medical records analyzed, 89.7% had an RTS value equal to 8, of these 77.9% were discharged and there was only 1 death. However, when we analyzed patients with RTS <4, who had a real indication for referral to a trauma center, we observed a 100% mortality rate. The RTS is a good scale to be used in health services, in view of the ease of its application, as well as being effective when evaluating the general mortality of the sample.
Keywords: Trauma; Trauma Severity Indices; Trauma Centers; CIENCIAS DA SAUDE::MEDICINA